2017
DOI: 10.1515/bhk-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Bobath and traditional approaches in post-stroke gait rehabilitation in adults

Abstract: SummaryStudy aim: The aim of this study was to compare the outcomes of a study of post-stroke gait reeducation using the Bobath neuro-developmental treatment (NDT-Bobath) method and the traditional approach. Material and methods: The study included 30 adult patients after ischemic stroke, aged 32-82. Patients were randomly assigned to one of the treatment groups: the study group (treated with the NDT-Bobath method combined with the traditional approach, ten sessions), and a reference group (treated with the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
0
12
0
3
Order By: Relevance
“…This method uses techniques based on facilitation, therapeutic manipulation and activation of key control points, aimed at improving patients' motor control while using the different stages of normal motor development as a guide (Balzer, 2018). The Bobath concept is as effective method as other therapies and can be considered more effective than a standard rehabilitation process for the treatment of the lower limbs (Mikołajewska, 2017;Gray and Ford, 2018). In addition, it significantly improves basic mobility skills and balance.…”
Section: Introductionmentioning
confidence: 99%
“…This method uses techniques based on facilitation, therapeutic manipulation and activation of key control points, aimed at improving patients' motor control while using the different stages of normal motor development as a guide (Balzer, 2018). The Bobath concept is as effective method as other therapies and can be considered more effective than a standard rehabilitation process for the treatment of the lower limbs (Mikołajewska, 2017;Gray and Ford, 2018). In addition, it significantly improves basic mobility skills and balance.…”
Section: Introductionmentioning
confidence: 99%
“…Стандартні підходи до реабілітації дітей дошкі-льного віку з ураженнями ЦНС передбачали прове-дення занять з лікувальної фізичної культури та лікувального дитячого масажу [13].…”
Section: Doclfc@uafmunclassified
“…При цьому ефект використан-ня методу Бобат, у порівнянні з традиційними під-ходами, є більш вагомим при тривалому застосу-ванні, що дозволяє стверджувати його суттєвий вплив на нормалізацію м'язового тонусу у ураже-них відділах нервово-м'язового апарату [16,17]. У даному випадку можна припустити більш оптима-льну аферентну пропріоцептивну імпульсацію, яка може сприяти відновленню рухової функції [13,17]. Не менш вагомим є вплив застосування методу Бобат на показник МТ, який не спостерігається при традиційних підходах до реабілітації.…”
Section: Doclfc@uafmunclassified
“…The studies conducted by Kılınç et.al ,2016, andLennon 2001 demonstrated that the individually developed bobath therapy exercise program improves trunk performance, balance, walking ability, more regular motor patterns and functional capabilities in stroke patients [10,14,15]. But few current systematic review studies performed by Díaz-Arribas et.al 2020, and Gray and Ford 2018 concludes that Bobath therapy alone is not more efficient than any other poststroke treatment [7,16].…”
Section: Introductionmentioning
confidence: 99%